ЗАСТОСУВАННЯ НАВЧАЛЬНИХ МАТЕРІАЛІВ МЕРЕЖЕВОЇ АКАДЕМІЇ CISCO ЯК ІНТЕГРОВАНА ЧАСТИНА ФАХОВИХ ПРЕДМЕТІВ ІТ (Innovative professional education, 2022)
The work highlights the experience of using and implementing thecourse of the Cisco network Academy «Introduction to IOT» (Introduction to IOT) asintegrated into the curriculum of the discipline «Computer systems and networks»specialty 015.39 «Professional education. Digital technologies» with a certificate aftersuccessfully studying at the Anton Makarenko Kyiv Vocational and PedagogicalCollege.
Keywords: student, college, Cisco Network Academy course